2018
DOI: 10.4103/wjnm.wjnm_47_17
|View full text |Cite
|
Sign up to set email alerts
|

Use of radioguided surgery in abdominal wall endometriosis: An innovative approach

Abstract: Endometriosis is characterized by the presence of endometrial glands and stroma outside the uterine cavity. The occurrence of endometriosis in the anterior abdominal wall is often associated with previous cesarean section, once the spread of endometrial cells during the surgical procedure is a biologically fact possible. A 43-year-old patient, with cesarean section history and pelvic endometriosis diagnosed for over 10 years, presented with progressive abdominal pain. Tests showed cystic image with 1.6 cm of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Farinazzo et al reported in 2018 the case of a 43-year-old patient with abdominal wall endometriosis, very symptomatic but not palpable. The use of ROLL in this case allowed rapid surgical identification of endometriotic lesion and its complete excision 14 . Manca et al 15 described in 2019 a peritoneal cytoreduction by ROLL, targeting 4 peritoneal metastasis and allowing proper identification of the recurrences.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Farinazzo et al reported in 2018 the case of a 43-year-old patient with abdominal wall endometriosis, very symptomatic but not palpable. The use of ROLL in this case allowed rapid surgical identification of endometriotic lesion and its complete excision 14 . Manca et al 15 described in 2019 a peritoneal cytoreduction by ROLL, targeting 4 peritoneal metastasis and allowing proper identification of the recurrences.…”
Section: Discussionmentioning
confidence: 87%
“…The use of ROLL in this case allowed rapid surgical identification of endometriotic lesion and its complete excision. 14 Manca et al 15 described in 2019 a peritoneal cytoreduction by ROLL, targeting 4 peritoneal metastasis and allowing proper identification of the recurrences.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 99%
“…Sclerotherapy with ultrasound guided injection into the lesion and high intensity focused ultrasound ablation used preoperatively appear to reduce bleeding and limit the size of the resection and decrease the risk of recurrence. (19) Endometriosis has a 1% risk of malignancy. 80% of malignancies occur in the ovary and 20% in other locations (including the abdominal wall).…”
Section: Discussionmentioning
confidence: 99%
“…Recientemente, Vitral, et al, 21 publicaron un reporte de caso de endometriosis de la pared abdominal no palpable clínicamente, en el que se realizó marcación prequirúrgica de la lesión mediante la técnica de ROLL TM (Radioguided Occult Lesion Localization) con el uso de tecnecio-99m, lográndose una resección de la lesión con adecuados márgenes.…”
Section: Discussionunclassified